Fluidos Ideais em Relatividade Geral e Cosmologia - Santos, Felipe de Melo (2016)
The matter content that permeates the universe is usually described by ideal fluids. Fluid dynamics is here reviewed, and an action for general ideal fluids is studied. It is shown that models of scalar fields minimally coupled, as the canonical scalar field and K-essence field, can mimic certain types of ideal fluids. The definitions of certain unusual fields, called ghosts and tachyons, are presented as part of the analysis of K-essence. At last, dynamical system theory is used to study these fluids on a cosmological background.